2016
DOI: 10.1159/000453181
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin Inhibits Electrophysiological Determinants of Excitatory and Inhibitory Synaptic Transmission in CA1 Pyramidal Neurons of Rat Hippocampal Slices: Reduction of These Effects by Edaravone

Abstract: Background: Streptozotocin (STZ) has served as an agent to generate an Alzheimer's disease (AD) model in rats, while edaravone (EDA), a novel free radical scavenger, has recently emerged as an effective treatment for use in vivo and vitro AD models. However, to date, these beneficial effects of EDA have only been clearly demonstrated within STZ-induced animal models of AD and in cell models of AD. A better understanding of the mechanisms of EDA may provide the opportunity for their clinical application in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Although, in our research, icv-STZ injection affected PS amplitude and fEPSP slope due to the application of paired-pulse stimulation protocols at IPIs of 20 and 30 ms (significantly), these difference in other IPIs was not noticeable. Other studies reported that the paired-pulse ratio (PPR) was decreased in response to STZ ( Moghaddam et al, 2013 ; Ju et al, 2016 ). However, our data suggest that both the icv-STZ model and STZ + α-Tocopherol may present post-synaptic–rather than pre-synaptic–plasticity dysfunctions and may indicate brain insulin resistance does not result in pre-synaptic impairments ( Srivareerat et al, 2011 ) which need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in our research, icv-STZ injection affected PS amplitude and fEPSP slope due to the application of paired-pulse stimulation protocols at IPIs of 20 and 30 ms (significantly), these difference in other IPIs was not noticeable. Other studies reported that the paired-pulse ratio (PPR) was decreased in response to STZ ( Moghaddam et al, 2013 ; Ju et al, 2016 ). However, our data suggest that both the icv-STZ model and STZ + α-Tocopherol may present post-synaptic–rather than pre-synaptic–plasticity dysfunctions and may indicate brain insulin resistance does not result in pre-synaptic impairments ( Srivareerat et al, 2011 ) which need further study.…”
Section: Discussionmentioning
confidence: 99%